Pengaruh Green Accounting, Good Corporate Governance, Free Cash Flow, dan Firm Size terhadap Financial Performance pada Perusahaan Perkebunan Kelapa Sawit yang Terdaftar di BEI Periode 2022 – 2024 - Bela Ramadani Zalza; Tri Astuti (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2026)
This study aims to determine the effect of green accounting, good corporate governance, free cash flow, and firm size on financial performance. The independent variables in this study consist of green accounting, good corporate governance, free cash flow, and firm size, while the dependent variable is financial performance. This study uses a quantitative method that begins with determining the best model to be used through panel data testing, followed by classical assumption testing, and hypothesis testing using Eviews 13 as a testing tool. The sampling technique used purposive sampling, resulting in a sample of 19 palm oil plantation companies listed on the Indonesia Stock Exchange for the 2022–2024 period, totaling 57 samples. This study found that green accounting negatively impacted financial performance. Meanwhile, free cash flow and firm size variables showed a positive influence on financial performance. However, good corporate governance did not affect financial performance. This study is expected to emphasize the quality of board decision-making, effective cash flow management, optimal asset utilization, and continued implementation of green accounting with a long-term strategy to improve financial performance.